Analysis of the Impact of Major Influencing Factors on the Waveform of the Surface Eddy Current Probe for Electroconductive Nonmagnetic Pipe Thickness; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Goldstein (Goldshtein) A. E. Aleksandr Efremovich (2016, 2016)
Title screen